Strength effects of the Copenhagen adduction exercise vs an adductor squeeze exercise in male football players - A randomized controlled trial - Pippas, C.; Gioftsos, G.; Korakakis, V.; Serner, A. (Science and Medicine in Football, 2025)
To examine the effect of assigning male football players to an 8-week Copenhagen Adduction (CA) and Adductor Squeeze (SQ) Pragmatic randomized controlled trial, 57 participants (16.7 ± 0.9 years, 175.9 ± 7.3 height and 66 ± 8.4 weight) were individually randomized to an 8-week progressive dynamic training protocol with the CA or an isometric training protocol with the SQ twice per week. Maximal eccentric (EHAD) and isometric (IHAD) hip adductor torque was tested with a handheld dynamometer. Perceived exertion and delayed onset muscle soreness (DOMS) were recorded throughout the intervention period. In the intention-to-treat analysis, no significant between-group difference was observed for EHAD (p = 0.478-0.833) nor IHAD (p = 0.084-0.118). There was a significant difference in DOMS between groups in the third to sixteenth exercise session, with the CA group reporting higher values (median varying between 0-3 vs 0-1, p = 0.000-0.009). Perceived exertion was greater for the CA group only in the fifteenth exercise session of the protocol (median of 4 vs 3, p = 0.031). No other significant differences between the groups were observed for DOMS nor perceived exertion. An 8-week adductor training program with either the Copenhagen Adduction or Adductor Squeeze exercise performed with two sets twice a week and adjusted for total volume did not result in significant differences in eccentric nor isometric adduction torque between the groups.